Pemetaan Sifat Fisik dan Kimia Tanah Pada Lahan Persawahan Di Kecamatan Kotamobagu Timur - Feronicha Efratha; Sandra E. Pakasi; Tilda Titah; Jemmy Najoan (Universitas Sam Ratulangi, 2019)
ABSTRACT The purpose of this research is to map the physical and chemical properties of soil on paddy fields in Kotamobagu Timur sub-district. This research was held in October to December 2019. This study used a survey method, in which soil samples were taken at 25 points spread over 658.17 ha or 27.78% of the area of East Kotamobagu District.Mapping conducted out in the Geospatial and Environmental sub-laboratory of the Faculty of Agriculture, Sam Ratulangi University. The outcome map of the physical properties of paddy soils in Kotamobagu Timur District is at texture class of clay and chemical properties of paddy soil with each respective criteria neutral soil pH, C-organic low to moderate, Nitrogen low to moderate, Phosphorus and Potassium currently being moderate. The situation of Nitrogen and C-organic for lowland rice plants is still in the low category. Keywords: Mapping, Paddy Fields, Physical Properties, Chemical Properties